From healing wounds to resorbable electronics, levan can fill bioadhesive roles in scores of markets - TOKSOY ÖNER, EBRU (IOP PUBLISHING LTD, 2019)
Levan is a fructose homopolysaccharide which gained attention recently for its unusual combination of properties distinguishing it from other natural biodegradable polysaccharides like chitosan, cellulose or starch. Among the strongest bioadhesives, film-forming levan is garnering interest for its role in some simple solutions to difficult problems. One of these is illustrated by the elegant research using laser-based techniques to construct levan films for healing wounds and burned tissue. Another is the development of bioresorbable electronic implants. Levan has been found in habitats as diverse as salterns and thermal waters to tropical plants and sugar factories. This review of the low viscosity, levan adhesive describes the mechanisms by which it forms bonds and the reasons behind some of its practical and industrial applications. Here we present descriptions from the literature for feasible approaches ready to transition from the laboratory to those searching for answers in fields as varied as medicine, packaging and furniture assembly.
Keywords: levan; fructan; polysaccharide; bioadhesive; natural adhesive; STRUCTURAL-CHARACTERIZATION; BIOMEDICAL APPLICATIONS; AZOTOBACTER-VINELANDII; MULTILAYER FILMS; MICROBIAL LEVAN; SULFATED LEVAN; FRUCTAN; PRODUCER; EXOPOLYSACCHARIDE; POLYSACCHARIDE